Perceptions of anesthesiologists on prevention and treatment of postoperative tremor - Bermejo Alvarez, Angelica (2024)
Introduction: Shivering or tremors are a very common clinical manifestation in the postoperative period of patients undergoing general or spinal anesthesia. Although hypothermia is the main risk factor for its occurrence, other contributing factors include the use of opioids, duration of surgery, administration of intravenous fluids at room temperature, among others. Objective: To establish the correlation between anesthesiologists' knowledge, attitudes, and practices regarding the prevention and treatment of postoperative shivering. Materials and Methods: An analytical observational correlation study was conducted with a sample of 35 professionals from major hospitals in Cuenca. A questionnaire designed by the author was used to collect data on knowledge, attitudes, and practices. Statistical analysis was performed using SPSS V 25. The study was approved by the Ethics Viability Committee (COIF) of the Faculty of Medical Sciences at UCE. Results: The sample was predominantly female (54.3%), with an average age of 40.89 years. A total of 31.4% had more than 10 years of work experience. Most professionals (57.1%) worked at the Social Security Hospital. Regarding knowledge, 60% had moderate levels; 51.4% had moderate ratings in attitudes, and 77.1% had moderate ratings in practices. A weak positive correlation (37%) was found between knowledge and attitudes (p:0.028), but no correlation was observed between knowledge and practices. Conclusion: There is a weak positive correlation between knowledge and attitudes regarding the prevention and treatment of postoperative shivering, but no correlation between knowledge and practices.